مؤشرات الرضا عن الحياة لدى امهات أطفال التوحد دراسة ميدانية بمركز التوحد بمدينة بوسعادة - بوبكري, فريجة (كلية العلوم الانسانية والاجتماعية جامعة محمد بوضياف المسيلة, 2020)
هدفت الدراسة الى الكشف على مستوى الرضا عن الحياة لدى امهات اطفال التوحد بمؤشراته الستة، (السعادة، الاجتماعية، الاستقرار النفسي، التقدير الاجتماعي، القناعة، الطمأنينة) وللتحقق من صحة هذه الاهداف تم الاعتماد على المنهج الوصفي، حيث انطلقت الدراسة من الاشكال التالي: ما مستوى الرضا عن الحياة لدى امهات اطفال التوحد؟ ويتفرع عنه التساؤلات الفرعية التالية: ما مستوى كل من (السعادة، الاجتماعية، الاستقرار النفسي، التقدير الاجتماعي، القناعة، الطمأنينة) لدى امهات اطفال التوحد بمركز التوحد بمدينة بوسعادة، وتكونت عينة الدراسة من (25) أم طفل توحدي، وتم اختيارها بطريقة العينة المتاحة، وتم استخدام مقياس الرضا عن الحياة حيث توصلت الدراسة للنتائج التالية: 1- أن مستوى تقييم درجة السعادة لدى أمهات أطفال التوحد جاء منخفضا. 2- أن مستوى تقييم درجة الاستقرار النفسي لدى أمهات أطفال التوحد جاء متوسطا. 3- أن مستوى تقييم درجة الاجتماعية لدى أمهات أطفال التوحد جاء متوسطا. 4- أن مستوى تقييم درجة التقدير الاجتماعي لدى أمهات أطفال التوحد جاء متوسطا. 5- أن مستوى تقييم درجة الطمأنينة لدى أمهات أطفال التوحد جاء متوسطا. 6- أن مستوى تقييم درجة القناعة لدى أمهات أطفال التوحد جاء متوسطا 7- أن مستوى الرضا عن الحياة لدى أمهات أطفال التوحد جاءت بدرجة متوسطة The study aimed to reveal the level of life satisfaction among mothers of autistic children with its six indicators, (happiness, social, psychological stability, social appreciation, contentment, reassurance). To verify the validity of these goals, the descriptive approach was based, where the study started from the following forms: What Level of life satisfaction for mothers of autistic children? It is divided into the following sub-questions: What is the level of each of (happiness, social, psychological stability, social appreciation, contentment, reassurance) among mothers of autistic children at the Autism Center in Bou Saada city, and the study sample consisted of (25) mothers of an autistic child, and it was chosen by the available sample method, and the measure of satisfaction with Life where the study reached the following results: 1- The level of the happiness rate rating for mothers of autistic children was low. 2- The level of evaluation of the degree of psychological stability of mothers of autistic children was average. 3- That the level of evaluation of the social degree of mothers of autistic children was average. 4- The level of assessment of the social assessment score of mothers of autistic children was average. 5- That the level of evaluation of the degree of reassurance of mothers of autistic children was average. 6- The level of evaluation of the degree of conviction of mothers of autistic children was average 7- The level of life satisfaction among mothers of autistic children was moderate.
Keywords: الرضا عن الحياة، التوحد، أمهات أطفال التوحد.life satisfaction, autism, mothers of autistic children.